Voices from the boundary line: The Australian Football League's Indigenous Team of the Century - Gorman, Sean (Routledge, 2012)
By engaging with all the members of the Australian Football League's (AFL) Indigenous Team of the Century named in August 2005, I provide an overview of Indigenous participation in Australian football, sport and Australian society in general. These players have been interviewed for an oral history project undertaken by the author. I discuss some of the specific themes and issues that Indigenous footballers have had to face and overcome, and the progress that the AFL has made in bringing Indigenous Australians into a mainstream consciousness. Further, I illustrate and demonstrate that, through Australian football, the marginalized history of Indigenous people can be told, understood and appreciated.